2017
DOI: 10.1177/1545968317746781
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin Predicts Long-Term Neurological Outcomes After Acute Spinal Cord Injury

Abstract: In spinal cord injury, serum albumin is an independent marker of long-term neurological outcomes. Serum albumin could serve as a feasible biomarker for prognosis at the time of injury and stratification in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
0
29
0
2
Order By: Relevance
“…Serum albumin also has been previously found to be significantly predictive of AIS grade improvement up to 52 weeks. 66 Platelets and gender also were only retained in models of SCIM. Previous studies contradict this result and have suggested that gender does not significantly correlate with functional neurology or independence.…”
Section: Discussionmentioning
confidence: 99%
“…Serum albumin also has been previously found to be significantly predictive of AIS grade improvement up to 52 weeks. 66 Platelets and gender also were only retained in models of SCIM. Previous studies contradict this result and have suggested that gender does not significantly correlate with functional neurology or independence.…”
Section: Discussionmentioning
confidence: 99%
“…6 Based on these papers, we can conclude that the use of biomarkers on blood and cerebrospinal fluid (CSF) to predict neurological injury and severity remains on translational research since a specific array of biomarkers needs to be designed and tested before widespread clinical use. [7][8][9][10][11] Since the initial review on assessment tools for acute SCI was presented by Hadley et al 12 in 2002, the ASIA Impairment Scale (AIS, short form for ASIA International Standards for Neurological Classification of Spinal Cord Injury [ISNCSCI]) has been designated as the recommended evaluation tool to evaluate and classify initial neurological impairment on admission and provide information on improvement at follow-up. The AIS comprises 5 grades of neurological injury: grade A, complete neurological injury (no motor or sensory function at S4, S5 segment); grade B, no motor function but preserved sensory function below the neurological injury with preservation including S3 and S4; grade C, incomplete neurological injury (with the preserved motor function below the neurological levhttps://doi.org/10.14245/ns.2040366.183…”
Section: Clinical Assessment and Classification Of Scimentioning
confidence: 99%
“…26 Therefore, our observed correlation between potassium and total motor score at 3 months is not unexpected. In a previous study involving 591 SCI patients, albumin was suggested to be an independent marker of long-term neurological outcome, 27 which may explain the correlation with 3 month outcome measures (except for pain scores). Other literature has also found notable alterations to RBC, hemoglobin, and hematocrit values in non-traumatic SCI, and has found that lymphocytes decreased over time in traumatic SCI.…”
mentioning
confidence: 98%